MANAJEMEN PENGELOLAAN BANK SAMPAH OLEH DINAS LINGKUNGAN HIDUP DAN KEBERSIHAN KOTA PEKANBARU TAHUN 2024 - Simanjuntak, Aloysius Wisely; ', Muchid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
Pekanbaru City is one of the largest cities with the highest waste generation in Riau Province in 2024. In addressing the problem of increasing waste, the Pekanbaru City Environmental and Sanitation Agency through waste banks strives to increase community participation and reduce waste generation in Pekanbaru City. However, the management of waste banks is not running optimally and maximally. The purpose of this study is to describe and analyze Waste Bank Management by the Pekanbaru City Environmental and Sanitation Agency in 2024. This study uses a qualitative approach with descriptive methods. In data collection, the author uses interview and documentation techniques in waste bank management at the Pekanbaru City DLHK. The results of the study based on four indicators in the theory of government management show that in the planning indicator, there is socialization carried out to the community, reactivating the Main Waste Bank (BSI), and forming around 300 Unit Waste Banks (BSU) in each sub-district, but in planning meetings the community has not been involved. In terms of organization, the waste bank's organizational structure has been established based on Regulation of the Minister of Environment and Forestry Number 14 of 2021 tentang Pengelolaan Sampah melalui Bank Sampah, and collaboration with the community has been established through a Memorandum of Understanding (MoU). However, in terms of implementation, Pekanbaru City's waste bank activities have not been running optimally due to limited facilities and differing budget allocations. Meanwhile, in terms of supervision, effective oversight has not yet been achieved, relying solely on monthly waste generation reports without concrete follow-up. Thus, It is necessary to implement more effective government management so that waste bank management in Pekanbaru City can run optimally and achieve the expected goals. Keywords: Waste Bank Management, Planning, Organizing, Actuanting, Controling